Perturbation of fermi resonance on hydrogen-bonded > C=O: 2D IR studies of small ester probes - Sakpal, Sushil; Chakrabarty, Suranjana; Reddy, Kambham Devendra; Deshmukh, Samadhan H.; Biswas, Rajib; Bagchi, Sayan; Ghosh, Anup (Journal of Physical Chemistry B, 2024)
We utilized linear and 2D infrared spectroscopy to analyze the carbonyl stretching modes of small esters in different solvents. Particularly noteworthy were the distinct carbonyl spectral line shapes in aqueous solutions, prompting our investigation of the underlying factors responsible for these differences. Through our experimental and theoretical calculations, we identified the presence of the hydrogen-bond-induced Fermi resonance as the primary contributor to the varied line shapes of small esters in aqueous solutions. Furthermore, our findings revealed that the skeletal deformation mode plays a crucial role in the Fermi resonance for all small esters. Specifically, the first overtone band of the skeletal deformation mode intensifies when hydrogen bonds form with the carbonyl group of esters, whereas such coupling is rare in aprotic organic solvents. These spectral insights carry significant implications for the utilization of esters as infrared probes in both biological and chemical systems.